PEMBIAYAAN PROPERTI DI PT. BPR SYARI’AH LANTABUR TEBUIRENG JOMBANG PERSPEKTIF HUKUM EKONOMI SYARI’AH - Dinda Amalia Kamila; Ninik Azizah (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine how the implementation of property financing at PT. BPR Syariah Lantabur Tebuireng Jombang and assess its compliance with the principles of Islamic Economic Law. The main focus of this study is to understand the practice of property financing applied in the institution and assess whether its implementation is in accordance with Islamic values. The method used is an empirical legal approach with a conceptual approach. The results of the study indicate that property financing at PT. BPR Syariah Lantabur Jombang is one form of fund distribution product (lending) through the musyarakah contract. From the perspective of Islamic Economic Law, PT. BPR Syariah Lantabur has implemented Islamic principles in real terms, both in its role as a financial intermediary institution and social intermediation. This is reflected in its operational activities and products that are in accordance with Islamic provisions and values.